(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was aimed to manufacture a margarine-like product in which the milk fat was replaced with olive oil at a rate of 25 and 50%, with the addition of monoglycerides (M.G.) as an emulsifying agent at a rate of 0.25%. The product was stored for 60 days. at State the temperature for storage. A cow butter sample was manufactured as control sample, and some properties were estimated, including the peroxide value and The acid value spreadability and hardness. Also, Sensory evaluation was carried out, and the research was conducted in the period from 1/10/2022 to 1/2/2023, The results showed that the M.G sample was lower in peroxide number, as the values for the M.G. sample ranged from 3.5 to 11.6), while in the butter sample it was 11 to 13.5 mEq O2/gm fat. The acid for the M.G. sample ranged between 0.84 and 1.4) and for the butter sample, it ranged between 0.84 and 1.6) mg KOH/gm fat. The spreadability was estimated at 20° for the M.G. sample, and it ranged from 3.4-5.15 cm, while in the butter sample it was between 2-3.25 cm. Hardness was also estimated, as it was about 2 cm in the M.G. sample at 20°, and in the butter, it was 0.7–1.15 cm.